Behavior of Ultrasensitive C-Reactive Protein in Myocardial Revascularization with and without Cardiopulmonary Bypass - Rafael Diniz Abrantes; Alexandre Ciappina Hueb; Whady Hueb; Fabio B. Jatene (Brazilian Journal of Cardiovascular Surgery)
Abstract Objective: To analyze the inflammation resulting from myocardial revascularization techniques with and without cardiopulmonary bypass, based on ultrasensitive C-reactive protein (US-CRP) behavior. Methods: A prospective non-randomized clinical study with 136 patients was performed. Sixty-nine patients were enrolled for Group 1 (on-pump coronary artery bypass - ONCAB) and 67 patients were assigned to Group 2 (off-pump coronary artery bypass - OPCAB). All study participants had blood samples collected for analysis of glucose, triglycerides, creatinine, total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL) and creatinephosphokinase (CPK) in the preoperative period. The samples of creatinephosphokinase MB (CKMB), troponin I (TnI) and US-CRP were collected in the preoperative period and at 6, 12, 24, 36, 48 and 72 hours after surgery. We also analyzed the preoperative biological variables of each patient (age, smoking, diabetes mellitus, left coronary trunk lesion, body mass index, previous myocardial infarction, myocardial fibrosis). All angiographically documented patients with >70% proximal multiarterial stenosis and ischemia, documented by stress test or classification of stable angina (class II or III), according to the Canadian Cardiovascular Society, were included. Reoperations, combined surgeries, recent acute myocardial infarction, recent inflammatory disease, deep venous thrombosis or recent pulmonary thromboembolism, acute kidney injury or chronic kidney injury were not included. Results: Correlation values between the US-CRP curve and the ONCAB group, the treatment effect and the analyzed biological variables did not present expressive results. Laboratory variables were evaluated and did not correlate with the applied treatment (P>0.05). Conclusion: The changes in the US-CRP at each moment evaluated from the postoperative period did not show any significance in relation to the surgical technique applied.